2015
DOI: 10.1371/journal.pmed.1001804
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Detection of and Early Response to Public Health Emergencies: Lessons from the West African Ebola Epidemic

Abstract: Mark Siedner and colleagues reflect on the early response to the Ebola epidemic and lessons that can be learned for future epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 16 publications
(15 reference statements)
2
64
0
1
Order By: Relevance
“…233,234 Such community action and "people science" played a major role in several areas to control the epidemic. 235 On a positive note, just as in the AIDS epidemic in Africa, for the first time during an outbreak of haemorrhagic fever, research was conducted successfully on vaccines, therapeutics, diagnostics, and social behaviour.…”
mentioning
confidence: 99%
“…233,234 Such community action and "people science" played a major role in several areas to control the epidemic. 235 On a positive note, just as in the AIDS epidemic in Africa, for the first time during an outbreak of haemorrhagic fever, research was conducted successfully on vaccines, therapeutics, diagnostics, and social behaviour.…”
mentioning
confidence: 99%
“…In the past 25 years, many international donors have committed such resources to improve laboratory capacity, but have done so with a focus on disease specific emergencies, such as human immunodeficiency virus epidemic. However, as the 2013–2016 Ebola virus disease epidemic and other outbreaks of emerging infectious diseases have highlighted, there remains a need to improve laboratory preparedness and practice on a global scale with a focus on laboratory capacity in a non-disease specific manner 30 . If the international health community is committed to disease detection, surveillance and pandemic preparedness, a more proactive approach is required.…”
Section: Discussionmentioning
confidence: 99%
“…No published studies of foreign government responses to 2014 Ebola were identified during this research. Public health experts' individual reasons for joining 2014 Ebola response missions have been evaluated (Rexroth et al, ), as have affected countries' own responses (Benton and Dionne, ) and WHO's response capabilities (Gronke, ; Osterholm, Moore, and Gostin, ; Siedner et al, ; van de Pas and van Belle, ). But the logics of donor countries' medical resource deployments also warrant exploration, given their importance to halting severe infectious disease epidemics.…”
Section: Five Political Perspectives On Hcw Deployment In Internationmentioning
confidence: 99%